Single-molecule localization microscopy in eukaryotes - Sauer, Markus; Heilemann, Mike (Chemical reviews, 2017)
Super-resolution fluorescence imaging by photoactivation or photoswitching of single fluorophores and position determination (single-molecule localization microscopy, SMLM) provides microscopic images with subdiffraction spatial resolution. This technology has enabled new insights into how proteins are organized in a cellular context, with a spatial resolution approaching virtually the molecular level. A unique strength of SMLM is that it delivers molecule-resolved information, along with super-resolved images of cellular structures. This allows quantitative access to cellular structures, for example, how proteins are distributed and organized and how they interact with other biomolecules. Ultimately, it is even possible to determine protein numbers in cells and the number of subunits in a protein complex. SMLM thus has the potential to pave the way toward a better understanding of how cells function at the molecular level. In this review, we describe how SMLM has contributed new knowledge in eukaryotic biology, and we specifically focus on quantitative biological data extracted from SMLM images.